Role of Pyroptosis and Ferroptosis in the Progression of Atherosclerotic Plaques - Yang, Zhen; Shi, Junhe; Chen, Li; Fu, Changgeng; Shi, Dazhuo; Qu, Hua (Frontiers in Cell and Developmental Biology, 2022)
Pyroptosis is a unique way of programmed cell death dependent on cysteinyl aspartate specific pro-teinase 1 (Caspase-1) in recent years. Ferroptosis was previously described as an iron-dependent non-apoptotic form of cell death. Both ways of cell death are believed to be closely related to the progression of atherosclerotic plaques, involving pyroptosis or ferroptosis in macrophages, smooth muscle cells, and vascular endothelial cells. Therefore, exploring the role of pyroptosis and ferroptosis in the development of atherosclerotic plaques may contribute to bringing new strategies for the treatment of atherosclerosis.